Ecological Index of Freshwater Gastropod in Buton Island, Southeast Sulawesi - Muhammad Fajar Purnama; Salwiyah Salwiyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
This research was conducted for 2 months (September-October 2021) and is located on Buton Island. The purpose of this study was to determine the diversity of freshwater gastropod species on Buton Island. Determination of the location for sampling gastropods using purposive sampling method (qualitative) and quantitative sampling using simple random sampling technique at locations that have been determined based on the presence of gastropods. Gastropod samples were collected manually (hand picking) using a paralone pipe (3.5 inches), Sieve (1 mm), and Gloves. The total number of gastropods obtained at 31 sampling locations on Buton Island was 4250. Buton Island gastropods consist of 24 genera and 55 species spread over 10 families, namely Achantinidae, Ampullariidae, Ariophantidae, Cyclophoridae, Lymnaeidae, Neritidae, Pachychilidae, Planorbidae, Thiaridae, and Viviparidae. The average abundance of gastropods reached 137,097 ind./m2 and the abundance of gastropod species ranged from 0.28-25 ind./m2. Overall, the results of the gastropod ecological index analysis showed a stable condition, where the diversity of gastropod species was categorized as high (H' = 3.31), moderate evenness (E = 0.83), high species richness (R = 6.46), dominance showed that there were no dominant species (C = 0.03) and the distribution of gastropods showed a clumped pattern (Ip = 0.02). The majority of Buton Island gastropod communities occupy rocky rivers and currents, a few of them live in artificial inland waters such as rice fields, embankments, dams/dams, and drainages and some are terrestrial snails.